The application of Phase 0 and microtracer approaches in early clinical development: past, present, and future - Roffel, A. F.; Hoogdalem, E.-J. van (Frontiers in Pharmacology, 2024)
Phase 0 microdosing studies were introduced to the drug development community some 20 years ago. A microdose was defined as less than 1/100th of the dose calculated based on animal data to yield a pharmacologic effect in humans, with a maximum of 100 µg, or 30 nmoles for protein products. In our experience, Phase 0 microdose studies have not been fully embraced by the pharmaceutical industry. This notion is based on the number of Phase 0 studies that we have been involved in. Thus, we conducted at least 17 Phase 0 microdose studies in the Zero's (on average 2 per year), but in the years beyond this was only 15 studies (1.4 per year); in these latter years, we did conduct a total of 23 studies which employed iv microdose for absolute bioavailability (ABA) assessments (2 per year on average), which are the most used and potentially informative type of clinical study using a microdose; albeit that they are formally not microdose studies. In the current review, we summarize past use of and experience with Phase 0 microdose designs in early clinical development, including intravenous 14C microdose absolute bioavailability (ABA) studies, and assess what is needed to increase adoption of useful applications of Phase 0 / microdose studies in the near future.